Modern trends in the formation and development of the scientific and educational environment of a higher educational institution - M. P. Shyshkina (Academy of Cognitive and Natural Sciences, 2013)
Trends in the development of big technologies determine the growth of their role in the development of mankind. This necessitates the modernization of the educational and scientific environment of a higher education institution in order to bring it in line with the modern level of science and technology development. It is cloud technology, which is now the most advanced technology of the information society itself, can play the role of the leading instrument of informatization of higher education.